The Everglades - Lynch , Wayne; Rainwater, Lois A. (UK : Northworld, 2007)
Photography, first-person anecdotes, and factual information on the animals, plants, climate and landscape come together to give a complete picture of the ecosystem in action.
Keywords: habitats -- non-fiction